Advances in Air–Sea Interactions, Climate Variability, and Predictability - Wei Zhang; Yulong Yao; Duo Chan; Jie Feng (Atmosphere)
Air–sea interaction remains one of the most dynamic and influential components of the Earth’s climate system, significantly shaping the variability and predictability of both weather and climate [...]